Communication - Cartwright, Roger (ExpressExec leading, 2002)
Fast track route to mastering all aspects of successful communication. Covers the key areas of communication, from knowing your audience to understanding body language, and from building networks of contacts to using stories. Examples and lessons from benchmark businesses, including American Express and The Body Shop and ideas from the smartest thinkers, including Naomi Klein, Richard Lewis and Frances Cairncross. Includes a glossary of key concepts and a comprehensive resources guide.